CLINICAL EFFECTIVENESS AND SAFETY OF IVABRADINE USE IN PATIENTS WITH UNSTABLE ANGINA AND DIABETES MELLITUS TYPE 2 - A. I. Kondratiev (Klinicist, 2014)
Aim – to estimate the clinical and pharmacological effects of ivabradine in complex treatment of patients with acute coronary syndrome and diabetes mellitus type 2 (DM 2). Materials and methods. The study included 36 patients with acute coronary insufficiency (unstable angina) and acute left ventricular failure (Killip class I–III) during concomitant type 2 diabetes. Results. Prescribing ivabradine in treatment of unstable angina pectoris complicated by type 2 diabetes led to decrease in clinical symptoms, heart rate and reduce in number of myocardial ischemia episodes. Patients treated with ivabradine, showed a significant tendency to increase left ventricular ejection fraction (12.3 %). Mo adverse reactions were recorded, including hypotensive complications. Conclusion. Ivabradine therapy was characterized by high ischemic and antianginal efficacy, good tolerability, did not lead to the development of tolerance and was not accompanied by the appearance of withdrawal syndrome.